Hardened hearts and cries for freedom: interpreting biblical narratives in a pandemic - Hillis, Mark K. (British Journal of religious education, 2024)
The impact of the COVID-19 pandemic in Australia has exposed social fault-lines and inequities not often recognised in such an affluent country. This study explores the relevance of Bible stories about plagues and disasters for the work of preachers, teachers, and pastoral practitioners who were independent voluntary contributors to this study. Each of them was serving with the Uniting Church in Australia (UCA) in settings where worship and learning take place. From within the activities of a particular Christian tradition, this article offers examples of practice and interpretive processes used in approaching the questions raised as an unfolding narrative. How did the use of Christian and Jewish Scriptures by these practitioners during the pandemic inform their worship, teaching, learning and social interactions? Examples were brought into dialogue with the work of biblical commentators on texts such as Exodus, Psalms, Prophets, and Gospels. The narrative hermeneutics of Paul Ricoeur and the biblical scholarship of Walter Brueggemann provided helpful conceptual anchorage for the task and assisted in broadening the perception of how local perspectives may or may not connect with global concerns.